Mapping the dynamics of teleost mucin biosynthesis in mucous cells under physiological and immersion vaccination conditions in flounder (Paralichthys olivaceus) - Jincheng Wang; Linhui Tao; Xiuzhen Sheng; Yingqin Liu; Xiaoqian Tang; Jing Xing; Heng Chi; Wenbin Zhan (Aquaculture, 2027)

Probing potential active sites and bipolar electric-field effects: Novel insights into the Li+ extraction mechanism on MoS2 in aqueous capacitive deionization - Xueli Zhang; Linhui Jia; Bing Chang; Dezhi Fang; Chengxing Cui; Silu Huo; Shuaiqi Ding; Yu Chen; Yang Li; Zhiyuan Chen; Runqiang Liu; Kexun Li (Desalination, 2026)

A ratiometric fluorescent probe with distinct response to Aflatoxin B1 and B2a: probe design, bioimaging, and quantification - Linhui Peng; Yuting Luo; Zhiqing Xun; Zhongyong Xu; Taoyuze Lv; Xinrong Du; Zhaohui Wang; Ya-Long Wang; Tianyi Qin; Bin Liu; Ming-Qiang Zhu (Food Chemistry, 2026)

Corrigendum to “Multi-task deep convolutional neural network for weed detection and navigation path extraction” [Comput. Electron. Agric. 229 (2025) 109776] - Yongda Lin; Lingxiao Wang; Shiyu Xia; Baiyu Qiao; Hu Han; Linhui Wang; Xiongkui He; Yajia Liu (Computers and Electronics in Agriculture, 2026)

Impact of nozzle orientation on jet characteristics of tilted narrow-throat pre-chambers - Linhui Huang; Qinglong Tang; Jiuling Sun; Xuze Zhu; Haifeng Liu; Mingfa Yao (Fuel, 2026)

Isostructural passivation strategy by 4,4′,4″-nitrilotribenzoic acid enhance interfacial compatibility for high-efficiency perovskite solar cells - Pihuang Yang; Ligang Yuan; Yuyan Dong; Linhui Tang; Junhong Duan; Weiqing Liu; Jianwei Chen; Chaohui Xiong; Ying Liu; Yan Liu; Wenhao Chen; Keyou Yan (Chemical Engineering Journal, 2026)

Precision interface architecture of zinc anodes for highly reversible Zn-metal batteries - Xijun Liu; Le Zhang; Xiaoru Chen; Linhui Chang; Zhifeng Xu; Qiangchao Sun; Xionggang Lu; Hongwei Cheng (Chemical Engineering Journal, 2026)

Eupatilin modulates the Mcl-1 ubiquitination status and PI3K/Akt/Foxo3a pathway to inhibit apoptosis and alleviate sepsis-induced acute myocardial injury - Linhui Shi; Panpan Liu; Longqiang Ye; Yiru Weng; Zhouzhou Dong (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Chrysin Attenuates Myocardial Cell Apoptosis in Mice - Gang Deng; Yongzheng Yang; Ouyang Qing; Jiang Linhui; Su Haotao; Chi Liu; Ge Li; Moussa Ide Nasser (Cardiovascular Toxicology, 2025)

Microbial community responses and functional shifts in carbon degradation driven by water-salt gradients in lakeshore wetlands of semi-arid lakes - Jialin Zhao; Xin Kou; Huamin Liu; Tiezheng Wu; Junyi Li; Yongman Wang; Hongliang Xie; Mingqi Wang; Linhui Wu; Lu Wen; Lixin Wang (Journal of Environmental Management, 2025)

Engineered albumin host for ratiometric fluorescent indicator-displacement assay: Distinguishing testosterone from estrone and estradiol - Yuting Luo; Linhui Peng; Zhang Lin; Zhiqing Xun; Na Li; Naiyu Liu; Yalong Wang; Xinfeng Du; Tianyi Qin; Bin Liu; Mingqiang Zhu (Chemical Engineering Journal, 2025)

The natural stable isotope index for de novo structural elucidation of phytomolecules with geographical and biological tracing - Xiaojing Yan; Xin Zhou; Mingyang Gong; Weidan Li; Mingyue Zhang; Tianci Huo; Xinyu Jiang; Xiaoyuan Hu; Xingchen Huang; Linhui Liu; Xue Feng; Qisong Zhang; et al. (Analytica Chimica Acta, 2025)

Vertical mixing of pollutants and secondary inorganic aerosol formations over Beijing, China - Jiannong Quan; Pengkun Ma; Yubing Pan; Siyu Cheng; Qianqian Wang; Linhui Lan; Lindong Dai; Yuzheng Wang; Yongchun Liu (Atmospheric Environment, 2025)

Investigation of soil physical, chemical and biological indicators in industrial towns: a case study in a Chinese town - Caixia Liu; Qingying Gao; Shuhe Zhang; Linhui Liao; Jingjing Chen; Liang Wang (Environmental Geochemistry and Health, 2025)

Mass spectrometric monitoring of redox transformation and arylation of tryptophan - Anji Gao; Yinghua Qi; Yixiang Luo; Xiaoyuan Hu; Ruowei Jiang; Shao Chang; Xin Zhou; Linhui Liu; Luping Zhu; Xue Feng; Ling Jiang; Hongying Zhong (Analytica Chimica Acta, 2025)

Hybrid crosslinking cellulose nanofibers-reinforced zwitterionic poly (ionic liquid) organohydrogel with high-stretchable, anti-freezing, anti-drying as strain sensor application - Dong Fu; Linhui Xing; Yang Xie; Peng Li; Fan Yang; Xin Sui; Jiaying Liu; Jialong Chi; Bo Huang; Jun Shen (Carbohydrate Polymers, 2025)

Dynamics of soil phosphorus fractions during the early recovery stage of two typical plantations in China after strip clearcutting - Linhui Zhang; Jihong Li; Su Chen; Wenlan Huang; Lulu Huang; Hongfeng Zhu; Yuanxiang Tang; Han Li; Chengming You; Lixia Wang; Sining Liu; Hongwei Xu; et al. (CATENA, 2025)

Multi-task deep convolutional neural network for weed detection and navigation path extraction - Yongda Lin; Shiyu Xia; Lingxiao Wang; Baiyu Qiao; Hu Han; Linhui Wang; Xiongkui He; Yajia Liu (Computers and Electronics in Agriculture, 2025)

A smartphone-based supramolecular biosensor for portable and rapid detection of buprofezin in real food samples - Yilin Zhan; Na Li; Tianyi Qin; Linhui Peng; Weihua Deng; Zhongyong Xu; Lei Wang; Immanuel David Charles; Bin Liu (Food Chemistry, 2024)

Thermal transformations of perfluorooctanoic acid (PFOA): Mechanisms, volatile organofluorine emissions, and implications to thermal regeneration of granular activated carbon - Junli Wang; Lillian N. Tran; Jose Mendoza; Kunpeng Chen; Linhui Tian; Yuwei Zhao; Jinyong Liu; Ying-Hsuan Lin (Journal of Hazardous Materials, 2024)

Combustion characteristics and flame development of ammonia in an optical spark-ignition engine - Jiuling Sun; Qinglong Tang; Mingsheng Wen; Linhui Huang; Haifeng Liu; Mingfa Yao (Fuel, 2024)

Exploring the material basis and molecular targets of Changma Xifeng tablet in treating Tourette syndrome: an integrative approach of network pharmacology and miRNA analysis - Jing Peng; Qiaoling Li; Linhui Liu; Ping Gao; Lipeng Xing; Li Chen; Hui Liu; Zhisheng Liu (Metabolic Brain Disease, 2024)

Enhanced uranium extraction using a nanostructured photothermal hydrogel membrane - Zhipeng Liu; Kai Feng; Xinle Zhang; Linhui Fu; Jiaxin Ren; Rui Gao; Shihao Ding; Wenqian Xing; Yiwen Li; Jiaji Cheng; Qiang Li; Jiang Gong; et al. (Chemical Engineering Journal, 2024)

Strategies and mechanisms for improving groundwater remediation efficiency of chlorinated ethenes by controlling the particle size of polyhydroxyalkanoate - Jie Ma; Linhui Lei; Zhiwei Gong; Zongping Wang; Hui Liu; Guanghao Chen; Gang Guo (Chemical Engineering Journal, 2024)

Influences of bragg reflection on harbor resonance triggered by irregular wave groups - Junliang Gao; Linhui Hou; Yingyi Liu; Huabin Shi (Ocean Engineering, 2024)

Exploring the relationship between lightning discharge current and plasma spectrum - Hong Deng; Facai Su; Ping Yuan; Baoyu Chen; Tingting An; Linhui Chen; Yingying An; Guorong Liu (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Cyanidin prevents cardiomyocyte apoptosis in mice after myocardial infarction - Deng Gang; Ouyang Qing; Yongzheng Yang; Muqaddas Masood; Yu-Hong Wang; Jiang Linhui; Su Haotao; Ge Li; Chi Liu; Moussa Ide Nasser; Ping Zhu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Monitoring system for peanut leaf disease based on a lightweight deep learning model - Yongda Lin; Linhui Wang; Tingting Chen; Yajia Liu; Lei Zhang (Computers and Electronics in Agriculture, 2024)

Impact of Climate Change on Water Diversion Risk of Inter‑Basin Water Diversion Project - Linhui Mu; Tao Bai; Dong Liu; Lei Li (Water Resources Management, 2024)

Time-sequenced hydrodynamics prediction system for underwater vehicles based on AI edge computing - Yuqing Hou; Fei Duan; Wenkang Zhu; Hui Li; Shengnan Shen; Xinhui Shen; Jiayue Wang; Yicang Huang; Wei Wei; Xin Liu; Linhui Liu (Ocean Engineering, 2024)

Comparative analysis of codon usage patterns in the chloroplast genomes of nine forage legumes - Mingkun Xiao; Xiang Hu; Yaqi Li; Qian Liu; Shaobin Shen; Tailing Jiang; Linhui Zhang; Yingchun Zhou; Yuexian Li; Xin Luo; Lina Bai; Wei Yan (Physiology and Molecular Biology of Plants, 2024)
Leguminosae is one of the three largest families of angiosperms after Compositae and Orchidaceae . It is widely distributed and grows in a variety of environments, including plains, mountains, deserts, forests, grasslands, and even waters where almost all legumes can be found. It is one of the most important sources of starch, protein and oil in the food of mankind and also an important source of high-quality forage material for animals, which has important economic significance. In our study, the codon usage patterns and variation sources of the chloroplast genome of nine important forage legumes were systematically analyzed. Meanwhile, we also constructed a phylogenetic tree based on the whole chloroplast genomes and protein coding sequences of these nine forage legumes. Our results showed that the chloroplast genomes of nine forage legumes end with A/T bases, and seven identical high-frequency (HF) codons were detected among the nine forage legumes. ENC-GC3s mapping, PR2 analysis, and neutral analysis showed that the codon bias of nine forage legumes was influenced by many factors, among which natural selection was the main influencing factor. The codon usage frequency showed that the Nicotiana tabacum and Saccharomyces cerevisiae can be considered as receptors for the exogenous expression of chloroplast genes of these nine forage legumes. The phylogenetic relationships of the chloroplast genomes and protein coding genes were highly similar, and the nine forage legumes were divided into three major clades. Among the clades Melilotus officinalis was more closely related to Medicago sativa , and Galega officinalis was more closely related to Galega orientalis . This study provides a scientific basis for the molecular markers research, species identification and phylogenetic studies of forage legumes.

KLF4 facilitates chromatin accessibility remodeling in porcine early embryos - Wei Zhu; Guowei Bu; Ruifeng Hu; Jixiang Zhang; Lianyong Qiao; Kai Zhou; Tingting Wang; Qiao Li; Jingjing Zhang; Linhui Wu; Yali Xie; Taotao Hu; et al. (Science China Life Sciences, 2024)

Quantification and characterization of microplastics in farmland soils of Jiangsu Province, East China - Bingqing Zhu; Ying Chen; Linhui Jiang; Cuicui Liu; Haimei Zhu; Dan Qiu; Shui Wang (Environmental Science and Pollution Research, 2023)

Response of soil phosphorus fractions to litter removal in subalpine coniferous forest - Linhui Zhang; Ya Shen; Yifan Hu; Jihong Li; Yao Liu; Su Chen; Lixia Wang; Sining Liu; Han Li; Chengming You; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2023)

In-depth urinary and exosome proteome profiling analysis identifies novel biomarkers for diabetic kidney disease - Shichun Du; Linhui Zhai; Shu Ye; Le Wang; Muyin Liu; Minjia Tan (Science China Life Sciences, 2023)

Coupling of soil methane emissions at different depths under typical coastal wetland vegetation types - Kun Li; Zihao Wang; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xiaoyan Shen; Xiaoya Xu; Qingfeng Chen (Chemosphere, 2023)

Arsenite exposure disturbs maternal-to-zygote transition by attenuating H3K27ac during mouse preimplantation development - Longtao Yu; Qiaoran Sun; Ziying Huang; Guowei Bu; Zhisheng Yu; Linhui Wu; Jingjing Zhang; Xia Zhang; Jilong Zhou; Xin Liu; Yi-Liang Miao (Environmental Pollution, 2023)

Observation of nitrogen oxide-influenced chlorine chemistry and source analysis of Cl2 in the Yangtze River Delta, China - Fangbing Li; Dan Dan Huang; Wei Nie; Yee Jun Tham; Shengrong Lou; Yuanyuan Li; Linhui Tian; Yuliang Liu; Min Zhou; Haichao Wang; Liping Qiao; Hongli Wang; et al. (Atmospheric Environment, 2023)

Direct conversion of CH4 and CO2 to alcohols using plasma catalysis over Cu/Al(OH)3 catalysts - Li Wang; Yuezhao Wang; Linhui Fan; Hongli Xu; Bowen Liu; Jiaren Zhang; Yimin Zhu; Xin Tu (Chemical Engineering Journal, 2023)

Soil nitrogen content and key functional microorganisms influence the response of wetland anaerobic oxidation of methane to trivalent iron input - Zihao Wang; Kun Li; Feifei Yan; Qingyue Xiang; Xinkun Zhao; Linhui Ji; Yu Xin; Jingyu Sun; Chenmiao Liu; Xinyi Xu; Ying Zhang; Xiaoyan Shen; et al. (Chemosphere, 2023)

Correction to: Have public environmental appeals inspired green total factor productivity? empirical evidence from Baidu Environmental Search Index - Linhui Wang; Bei Liu; Yongda He; Zhiqing Dong; Shixiang Wang (Environmental Science and Pollution Research, 2022)

Have public environmental appeals inspired green total factor productivity? empirical evidence from Baidu Environmental Search Index - Linhui Wang; Bei Liu; Yongda He; Zhiqing Dong; Shixiang Wang (Environmental Science and Pollution Research, 2022)

The construction of high precision geostrophic currents based on new gravity models of GOCE and satellite altimetry data - Wenyan Sui; Junru Guo; Jun Song; Zhiliang Liu; Meng Wang; Xibin Li; Yanzhao Fu; Yongquan Li; Yu Cai; Linhui Wang; Lingli Li; Xiaofang Guo; et al. (Acta Oceanologica Sinica, 2021)

Combined addition of chemical and organic amendments enhances plant resistance to aboveground herbivores through increasing microbial abundance and diversity - Linhui Jiang; Michael Bonkowski; Ling Luo; Paul Kardol; Yu Zhang; Xiaoyun Chen; Daming Li; Zhenggao Xiao; Feng Hu; Manqiang Liu (Biology and Fertility of Soils, 2020)

Unexpected rise of ozone in urban and rural areas, and sulfur dioxide in rural areas during the coronavirus city lockdown in Hangzhou, China: implications for air quality - Liqiang Wang; Mengying Li; Shaocai Yu; Xue Chen; Zhen Li; Yibo Zhang; Linhui Jiang; Yan Xia; Jiali Li; Weiping Liu; Pengfei Li; Eric Lichtfouse; et al. (Environmental Chemistry Letters, 2020)

Organic Matter Pollution During the Spring Thaw in Hulun Lake Basin: Contribution of Multiform Human Activities - Wenlin Wang; Wenjing Li; Yan Yan; Bo Liu; Tanjing Wang; Sichen Mao; Linhui Song; Huashan Dou; Wen Ao; Changxin Zou (Bulletin of Environmental Contamination and Toxicology, 2020)

Identification and functional characterization of squalene epoxidases and oxidosqualene cyclases from Tripterygium wilfordii - Yuan Liu; Jiawei Zhou; Tianyuan Hu; Yun Lu; Linhui Gao; Lichan Tu; Jie Gao; Luqi Huang; Wei Gao (Plant Cell Reports, 2020)

Danshen formula granule and salvianic acid A alleviate ethanol-induced neurotoxicity - Yujia Li; Hui Chen; Yating Yang; Menglan Niu; Jiaxin Wang; Yuanyuan Wu; Linhui Niu; Hongliang Liu; Dengke Bao (Journal of Natural Medicines, 2020)

Probing the function of protein farnesyltransferase in Tripterygium wilfordii - Ping Su; Linhui Gao; Shuang Liu; Hongyu Guan; Jian Wang; Yifeng Zhang; Yujun Zhao; Tianyuan Hu; Lichan Tu; Jiawei Zhou; Baowei Ma; Xihong Liu; et al. (Plant Cell Reports, 2019)

Gibberellin stimulates regrowth after defoliation of sheepgrass (Leymus chinensis) by regulating expression of fructan-related genes - Yueyue Cai; Linhui Shao; Xiuqing Li; Gongshe Liu; Shuangyan Chen (Journal of Plant Research, 2016)

Molecular diversity of 16S rRNA and gyrB genes in copper mines - Huaqun Yin; Linhui Cao; Guanzhou Qiu; Dianzuo Wang; Laurie Kellogg; Jizhong Zhou; Xinxing Liu; Zhimin Dai; Jiannan Ding; Xueduan Liu (Archives of Microbiology, 2008)